Financial Planning Information for Production Start-ups. - Harvey, David W. (The Accounting Review, 1976)
This paper presents special forms of the learning model relevant to production situations in which staffing levels constrain production for both the cumulative average case and the marginal average case. They are applicable to planning profits and cash flows and to the capital budgeting decision under simplifying assumptions about demand and working capital. In a later section. these forms have been modified to permit direct observation of effects of errors in learning model parameter estimates on profits, cash flows and internal rate of return.